Lean management and HRM practices in relation towards operational performance: confirmation of measurement model - Azhani, Ismail; Yuserrie, Zainuddin (Universiti Malaysia Pahang, 2018)
This study explores the influence of human resource management (HRM) practices on the adoption of lean management (LM) that affect operational performance (OP) in Malaysia local authorities (LAs). The purpose of this paper is to empirically investigate the latent constructs of and the scale for evaluating LM and HRM practices in relation towards OP in organization. This research analyzes the data using Partial Least Square-Structural Equation Modeling (PLS-SEM) and utilizes SmartPLS 3 to investigate the impact of HRM practices on LM and OP in organization. With data collected from 177 Malaysia LAs, a one-stage approach is conducted in the assessments of the measurement model through confirmatory factor analysis (CFA) and adjusted according to the guidelines set to verify reliability and validity. The empirical findings suggest that the measurement model demonstrates satisfactory reliability and validity. This study contributes to the literature on empirical examination of the constructs of LM, HRM practices and OP, and to the practices of managers with validated measurement scales to evaluate the strengths and weaknesses in different facets of implementing LM in improving OP through the role played by HRM practices in the organizations.